Import Processing and Trade Costs - Jerónimo Carballo; Alejandro Graziano; Georg Schaur; Christian Volpe Martincus (Center for Economic Studies and ifo Institute (CESifo), 2021)
Trade facilitation policy focuses on accelerated and transparent shipment processing to reduce trade costs. A common measure to evaluate processing frictions is the time it takes to import. In this paper we translate import processing times to costs. Our theory considers that shipment processing times at the port of entry are random and firms choose lead times to buffer processing shocks. Based on this theory, we employ detailed data on import processing dates, instrumental variables, and firm-product-origin level import data to estimate import processing costs. Evaluated at the median, import processing is equivalent to a 20 percent import tariff. For experienced importers, the import processing cost tariff drops to about 12 percent. Our time cost estimate generalizes existing approaches in the literature. We show that our extensions are economically relevant to determine import processing costs, predict who would benefits from trade facilitation, and interpret existing data on the time it takes to import.
Keywords: F10; F13; F14; 330; trade costs; border processing; trade policy